If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 3y = 40 Solving 9x + 3y = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 9x + 3y + -3y = 40 + -3y Combine like terms: 3y + -3y = 0 9x + 0 = 40 + -3y 9x = 40 + -3y Divide each side by '9'. x = 4.444444444 + -0.3333333333y Simplifying x = 4.444444444 + -0.3333333333y
| t=-15t^2+135t+10 | | 4y^2-12y+9-y^2=9 | | 9z+3y=40 | | 6x-3x=20 | | (x+15)=(4x-15) | | r-10=-3 | | 0.6x-1.8=1.2x | | x-y=-29 | | (2x-1)=10 | | 6x+12(3x+3)=18(3x+2) | | rx+sy=c | | 5x-2y=17 | | x+5y=-24 | | X-7y=-19 | | 9x-(3x+2)=7x-29 | | 6x+y=47 | | 2x+j=-3 | | -4x+42= | | -4x^2-2x+2=0 | | 17*x-8=40+x | | 8x^2+34x-9=0 | | 25t^2-125t+150=0 | | 15+.50m=2.5+.25m | | y+5-5=3-5 | | (10x+7)(3x-9)=0 | | X^3+2X^2-2X-2=0 | | 3x-j=18 | | x^2-y^2=9 | | 2x(-1.5)+y-2y=-3 | | 2x-2y=(-3) | | Y^2-10y+9=0 | | 12x^2-27x+6=0 |